2014
DOI: 10.1111/irv.12289
|View full text |Cite
|
Sign up to set email alerts
|

A novel highly pathogenic H5N8 avian influenza virus isolated from a wild duck in China

Abstract: Migrating wild birds are considered natural reservoirs of influenza viruses and serve as a potential source of novel influenza strains in humans and livestock. During routine avian influenza surveillance conducted in eastern China, a novel H5N8 (SH-9) reassortant influenza virus was isolated from a mallard duck in China. blast analysis revealed that the HA, NA, PB1, PA, NP, and M segments of SH-9 were most closely related to the corresponding segments of A/duck/Jiangsu/k1203/2010 (H5N8). The SH-9 virus prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 17 publications
(34 reference statements)
0
49
0
Order By: Relevance
“…(27,28). Since 2010, its inner-clade 2.3.4.4 H5 reassortants, which include H5N2, H5N6, and H5N8 viruses, are frequently found in waterfowl and terrestrial poultry in China and other Asian countries (8,29,30). By 2014, H5N2 and H5N8 viruses had spread by migratory birds to poultry in multiple continents (10).…”
Section: Discussionmentioning
confidence: 99%
“…(27,28). Since 2010, its inner-clade 2.3.4.4 H5 reassortants, which include H5N2, H5N6, and H5N8 viruses, are frequently found in waterfowl and terrestrial poultry in China and other Asian countries (8,29,30). By 2014, H5N2 and H5N8 viruses had spread by migratory birds to poultry in multiple continents (10).…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem for vaccine development in the interpandemic period is an unknown influenza strain to target. Since 1996, H5N1 has diversified into numerous phylogenetic groups with drifted H5 antigens, while recent outbreaks have occurred from H7N9 and H5N8 subtypes [15][16][17]. Zoonotic vaccines derived from current or historic avian influenza strains may not offer protection from a future pandemic strain.…”
Section: Avian Influenza Vaccinementioning
confidence: 99%
“…In January 2014, novel reassortant HPAI viruses of subtype H5N8, clade 2.3.4.4, were detected in poultry and wild bird carcasses in South Korea ( 2 ). Closely related viruses were also detected in Japan ( 3 ) and China ( 4 ). Genetic analysis showed that this virus was generated by reassortment of HPAI viruses of eastern China.…”
mentioning
confidence: 99%